2009
DOI: 10.4103/1596-3519.59573
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and knowledge of mother-to-child transmission of HIV among mothers attending the pediatric HIV clinic, Kano, Nigeria

Abstract: Background: Nigeria accounts for about 10%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 6 publications
4
11
2
1
Order By: Relevance
“…This is in consonance with a similar study conducted by Adeleke et al in Kano northern Nigeria who reported inadequate awareness of women on MTCT [30] Even non pregnant women in the study did not demonstrate sufficient awareness of MTCT. About 52.2% showed that they were aware that HIV can be transmitted to the child while breastfeeding, while 28.2% among them were aware the risk of MTCT can be reduced by mothers taking anti retro viral drugs during pregnancy.…”
Section: Discussionsupporting
confidence: 89%
“…This is in consonance with a similar study conducted by Adeleke et al in Kano northern Nigeria who reported inadequate awareness of women on MTCT [30] Even non pregnant women in the study did not demonstrate sufficient awareness of MTCT. About 52.2% showed that they were aware that HIV can be transmitted to the child while breastfeeding, while 28.2% among them were aware the risk of MTCT can be reduced by mothers taking anti retro viral drugs during pregnancy.…”
Section: Discussionsupporting
confidence: 89%
“…All the patients at stage I were women and 28 of 51 HIV patients in this study were female. This showed that many HIV infected female patients were infected with HIV infection or sought for active HIV treatment at early stage (Adeleke et al, 2009). However, less women (2 of 6) patients were using complementary therapy and few female patients presented at advanced stage of HIV infection (WHO staging IV) in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Adeleke et al on awareness and knowledge of MTCT of HIV among mothers attending a pediatric HIV clinic in northern Nigeria also found that more than half of the respondents had no idea on MTCT; only 6 and 24% knew cesarean section and avoiding breastfeeding, respectively, could have roles to play in MTCT. 11 This pattern of poor comprehensive knowledge about MTCT of HIV has been identified by previous studies both within and outside Nigeria. 12,13 64% of study population felt that mother to child transmission is preventable.…”
Section: Discussionmentioning
confidence: 77%